y = 2/3x + 7
g(x) = (x + 9)^2 − 4
g(x) = (x − 4)^2 + 9
g(x) = (x + 4)^2 + 9
Answer:
Step-by-step explanation:
Hello,
We know that (let's assume that x is different from 0 as we cannot divide by 0)
and we want to estimate
Let's take the square.
So, we can write
Hope this helps.
Do not hesitate if you need further explanation.
Thank you
Answer:
$1.20
Step-by-step explanation:
Mandy and Jordan each bought some of the same notebooks and the same three-ring binder.
Mandy paid for 3 notebooks and 1 binder = $5.85
Jordan paid for 2 notebooks and 1 binder = $4.65
Mandy paid more money for extra one notebook = 5.85 - 4.65
= $1.20
Therefore, the price of one notebook is $1.20.